Legislation That Limits Economic Law Implementation - Suwinto Johan (Fakultas Hukum, Universitas Warmadewa, 2023)
The goal of government intervention is to protect society's interests. The government acts in accordance with prevailing laws and regulations. The goal of economics is to earn as much money as possible. As a result of government intervention, corporate players' incomes will be reduced. The research aim is to examine the impact of government intervention in the form of laws and regulations on economic principle. This study employs a normative legal approach. The result shows that the profit maximization principle, which claims that business actors should maximize profits, does not apply to commodities or important societal requirements. Conditions influence the community's basic requirements. Masks and Covid-19 medications are essential items for the community during the Covid-19 pandemic. The government's intervention must be based on prevailing law and regulations. When it comes to market circumstances, government involvement isn't always effective.